Tata Kelola Pemerintahan Kolaboratif dalam Pengembangan Sektor Pariwisata di Kabupaten Mahakam Ulu - Sophia Hipui (Dinasti Review, 2024)
Tourism is one sector that is receiving attention from the government to continue to be developed considering its potential contribution to the economy. Moreover, for Mahakam Ulu Regency, which in fact is a state border area, efforts are being made to explore its potential in the tourism sector with development measures. The hope is none other than to provide an increase in the standard of living for the people of Mahakam Ulu Regency. With the limitations of the regional government, the development of the tourism sector in Mahakam Ulu Regency is oriented towards collaborative governance mechanisms. This article aims to explain collaborative governance in developing the tourism sector in Mahakam Ulu Regency. To answer the research objectives, a qualitative approach was applied with data collected from various secondary sources. The results of the analysis show that collaborative governance in the development of the tourism sector in Mahakam Ulu Regency shows the participation of various actors such as the central government, regional government, community and private sector with the central government and regional government having a role in directing and empowering the resources they have which then have an impact in improving the standard of living of the community, the community is more oriented towards matters relating to community empowerment itself, and the private sector is expected to invest in advancing the tourism sector in Mahakam Ulu Regency. Among these four actors, the realization of collaborative governance will be seen if all of these actors create principles of engagement, shared motivation, and capacity for joint action.c